A CONFIRMATORY APPROACH TO DIAGNOSING WELL-DIFFERENTIATED LIPOSARCOMA USING LIMITED BIOPSY TISSUE. (February 2015) - Sun, Yi Qiu; Jones, Wayne
Abstract : Aim: To demonstrate a confirmatory approach to diagnosing a well-differentiated liposarcoma using limited biopsy tissue. Methods: A 66-year-old man presenting with pneumonia had an incidental CT finding of a 20 cm heterogeneous fat-density mass within the central mediastinum. The mass showed low PET FGD-avidity. The radiological characteristics and location suggested a liposarcoma. Mediastinoscopic biopsy yielded limited lesional tissue, further analysed by light microscopy on H&E and IPX stains, and FISH analysis for MDM2-gene amplification. Results: Microscopically, the lesional tissue resembled an adipocytic lesion comprising mature adiopocytes with significant variability, nuclear atypia, with occasional lipoblasts, and fibromyxoid stroma. However, necrosis, mitosis and dedifferentiated areas were not identified. The lesional cells showed positive staining for MDM2 and negative staining for CD34, S-100, HMB45, cytokeratins and calretinin. FISH analysis revealed MDM2-gene amplification, confirming the diagnosis of a well-differentiated liposarcoma. Dedifferentiated areas were identified on subsequently resected tumour. Discussion: The diagnosis of well-differentiated liposarcoma on biopsy is sometimes difficult with limited and poorly representative tissue. Whilst location and radiological appearance may be suggestive, a selective IPX panel and MDM2 FISH analysis can offer a definitive diagnosis.